Shielding Electric Fields to Prevent Coalescence of Emulsions in Microfluidic Channels Using a 3D Metallic Coil - Jingmei Li; Zhou Liu; Haibo Huang; Ho Cheung Shum (Micromachines, 2015)
In microfluidics, electric fields are widely used to assist the generation and the manipulation of droplets or jets. However, uncontrolled electric field can disrupt the operation of an integrated microfluidic system, for instance, through undesired coalescence of droplets, undesired changes in the wettability of the channel wall or unexpected death of cells. Therefore, an approach to control the distribution of electric fields inside microfluidic channels is needed. Inspired by the electro-magnetic shielding effect in electrical and radiation systems, we demonstrate the shielding of electric fields by incorporating 3D metallic coils in microfluidic devices. Using the degree of coalescence of emulsion drops as an indicator, we have shown that electric fields decrease dramatically in micro-channels surrounded by these conductive metallic coils both experimentally and numerically. Our work illustrates an approach to distribute electric fields in integrated microfluidic networks by selectively installing metallic coils or electrodes, and represents a significant step towards large-scale electro-microfluidic systems.